ROS Mediate xCT-Dependent Cell Death in Human Breast Cancer Cells under Glucose Deprivation - Mei-Chun Chen; Li-Lin Hsu; Sheng-Fan Wang; Chih-Yi Hsu; Hsin-Chen Lee; Ling-Ming Tseng (Cells, 2020)
xCT, also known as solute carrier family 7 member 11 (SLC7A11), the light chain of the cystine/glutamate antiporter, is positively correlated with cancer progression due to antioxidant function. During glucose deprivation, the overexpression of xCT does not protect cancer cells but instead promotes cell death. Further understanding the mechanism of glucose deprivation-induced cell death is important for developing anticancer treatments targeting the glucose metabolism. In this study, we found that breast cancer cells with a high expression of xCT demonstrated increased levels of reactive oxygen species (ROS) and were more sensitive to glucose deprivation than the cells with a low expression of xCT. However, AMP-activated protein kinase (AMPK) did not significantly affect glucose-deprivation-induced cell death. The antioxidant N-acetyl-cysteine prevented glucose-deprivation-induced cell death, and the glutathione biosynthesis inhibitor L-buthionine-S, R-sulfoximine enhanced glucose-deprivation-induced cell death. The inhibition of xCT by sulfasalazine or a knockdown of xCT reduced the glucose-deprivation-increased ROS levels and glucose-deprivation-induced cell death. Glucose deprivation reduced the intracellular glutamate, and supplementation with α-ketoglutarate prevented the glucose-deprivation-increased ROS levels and rescued cell death. The knockdown of sirtuin-3 (SIRT3) further enhanced the ROS levels, and promoted xCT-related cell death after glucose deprivation. In conclusion, our results suggested that ROS play a critical role in xCT-dependent cell death in breast cancer cells under glucose deprivation.